Management Implications for the Korean Wave - Jeong-Seob Kim; Joo-Yeun Park (International Telecommunications Society (ITS), 2018)
Based on Penrose's resource-based theory (RBT), this paper aims to examine the resource and performance structures of South Korean entertainment firms, which are driving the Korean Wave, or K-culture, and arrive at the management implications of the finding. The analysis of the 2011 and 2012 management structures of all 11 listed Korean entertainment firms shows low degree of matching between individual resources and insufficient interconnectedness between resources and performance. Sustainable management began to be discussed in the industry during this period due to checks by neighboring countries such as China and Japan. This calls for specialized and scientific management of resources by entertainment firms in order to better leverage their resources and raise the resources' direct contribution to creating new resources and enhancing performance.
Keywords: 330; Korean Wave; K-Culture; entertainment firms; Resource-Based Theory (RBT); resources; performance